2021
DOI: 10.3892/ijmm.2021.4872
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin reverses TNF‑α induced osteogenic damage to human periodontal ligament stem cells by suppressing the NF‑κB/NLRP3 inflammasome pathway

Abstract: Quercetin (Quer) is a typical antioxidant flavonoid from plants that is involved in bone metabolism, as well as in the progression of inflammatory diseases. Elevated levels of tumor necrosis factor-α (TNF-α), a typical pro-inflammatory cytokine, can affect osteogenesis. In the present study, TNF-α was used to establish an in vitro model of periodontitis. The effects of Quer on, as well as its potential role in the osteogenic response of human periodontal ligament stem cells (hPDLSCs) und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…In this study, our results indicated that Quercetin functions as a regulator of inflammation through modulating NF-kB and cytokine production in macrophages upon oral microbial infection. These findings are consistent with previous mechanistic studies which revealed that Quercetin attenuates inflammation through interfering with multiple signaling pathways including NF-kB, mitogen-activated protein kinase (MAPK), phosphatidylinositol-3-kinase/Akt (PI3K/Akt), signal transducer and activator of transcription proteins (STAT), inflammasome complex and regulates cellular functions including apoptosis, cellular senescence, and autophagy in several models of diseases and cell types (100)(101)(102)(103)(104)(105)(106)(107)(108). Notably, the beneficial role of Quercetin has also been extensively studied in cancer, and the potent antiinflammatory and anti-tumor functions have been documented in breast cancer and liver cancer through its ability to inhibit NF-kB signaling cascade (109,110).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, our results indicated that Quercetin functions as a regulator of inflammation through modulating NF-kB and cytokine production in macrophages upon oral microbial infection. These findings are consistent with previous mechanistic studies which revealed that Quercetin attenuates inflammation through interfering with multiple signaling pathways including NF-kB, mitogen-activated protein kinase (MAPK), phosphatidylinositol-3-kinase/Akt (PI3K/Akt), signal transducer and activator of transcription proteins (STAT), inflammasome complex and regulates cellular functions including apoptosis, cellular senescence, and autophagy in several models of diseases and cell types (100)(101)(102)(103)(104)(105)(106)(107)(108). Notably, the beneficial role of Quercetin has also been extensively studied in cancer, and the potent antiinflammatory and anti-tumor functions have been documented in breast cancer and liver cancer through its ability to inhibit NF-kB signaling cascade (109,110).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, previous reports have found that quercetin can inhibit the release of inflammatory cytokines in human gingival fibroblasts (HGFs) stimulated by Porphyromonas gingivalis lipopolysaccharide in vitro and alleviate alveolar bone resorption in in vivo animal models [ 14 , 15 , 16 , 17 ]. Although several studies identify QUE as a promising phytochemical to sustain periodontal tissue health, the poor bioavailability, high metabolic rate, and rapid clearance from body of QUE limit its clinical application [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a novel cell-free therapy, exosomes derived from MSCs (MSC-Exo) not only have immuno-inflammatory and modulatory capabilities similar to those of MSCs but also overcome numerous disadvantages of cellular therapy ( Jafarinia et al, 2020 ). Previous studies have found that exosomes derived from GMSCs (GMSC-Exo) can inhibit the activation of M1 macrophages and attenuate the inflammatory response ( Wang et al, 2020 ; Zhang W et al, 2021 ). It has been demonstrated that GMSC-Exo play an important role in chondrogenesis ( Mao et al, 2018 ), wound healing ( Shi et al, 2017 ; Kou et al, 2018 ), preventing periodontal bone loss ( Nakao et al, 2021 ), promoting rat sciatic nerve regeneration ( Rao et al, 2019 ), and taste bud regeneration ( Zhang Y et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%